Electrically Driven Microcavity Exciton-Polariton Optomechanics at 20 GHz ELECTRICALLY DRIVEN MICROCAVITY EXCITON-POLARITON ... KUZNETSOV et al. - Kuznetsov, Alexander S.; Machado, Diego H. O. [UNESP]; Biermann, Klaus; Santos, Paulo V. (American Physical Society (APS), 2021)
Microcavity exciton polaritons enable the resonant coupling of excitons and photons to vibrations in the super-high-frequency (SHF, 3-30 GHz) domain. We introduce here a novel platform for coherent SHF optomechanics based on the coupling of polaritons and electrically driven SHF longitudinal acoustic phonons confined in a planar Bragg microcavity. The highly monochromatic phonons with tunable amplitudes are excited over a wide frequency range by piezoelectric transducers, which also act as efficient phonon detectors with a very large dynamical range. The microcavity platform exploits the long coherence time of polaritons as well as their efficient coupling to phonons. Furthermore, an intrinsic property of the platform is the backfeeding of phonons to the interaction region via reflections at the sample boundaries, which leads to quality factor × frequency products (Q×f) exceeding 1014 Hz as well as huge modulation amplitudes of the optical transition energies exceeding 8 meV. We show that the modulation is dominated by the phonon-induced energy shifts of the excitonic polariton component. Thus, the large modulation leads to a dynamical switching of light-matter nature of the particles from a mixed (i.e., polaritonic) one to photonlike and excitonlike states at frequencies up to 20 GHz. On the one hand, this work opens the way for electrically driven polariton optomechanics in the nonadiabatic, sideband-resolved regime of coherent control. Here, the bidirectionality of the transducers can be exploited for light-to-sound-to-rf conversion. On the other hand, the large phonon frequencies and Q×f products enable phonon control with optical readout down to the single-particle regime at relatively high temperatures (of 1 K).